Isolation and identification of Citrobacter freundii from chicken meat samples using cultural and molecular techniques - Hashim, Mohammed Hayder; AlKhafaji, Marwa Hameed (Iraqi Journal of Science, 2018)
Because of Citrobacter freundii medical and economical importance and that there are only little local studies about it, this study aimed to isolate and identify this important bacterial species from others that have a similar biochemical and morphological characteristics. Twenty five chicken meat samples were collected randomly from local markets in Baghdad city during 2017; Citrobacter was isolated from the collected samples using selective and differential media and identified using biochemical tests, the identification was confirmed using Vitek 2 compact and polymerase chain reaction for 16S rRNA and the isolated bacteria identified as C. freundii.